A critical-contextual approach in comparative migration law. (27th January 2023) - Hinterberger, Kevin Fredy
This contribution deals with the critical-contextual method, which is a critical evolution of functionalism and introduced as a specific comparative law approach to migration law. Critical-contextual comparison draws upon three established methods/approaches: functionalism, contextualism and critical approaches. It fuses them to qualify as 'thick' comparison per Frankenberg. Comparisons are 'thick' if they are context-sensitive, critical and reflexive. To contribute to the operation and application of the critical-contextual approach generally, the present article carves out the method of critical-contextual comparison relying on certain findings of a case study on regularisations of irregularly staying migrants in the EU, in particular in Germany, Austria and Spain. The aim is to demonstrate how critical-contextual comparison can be undertaken in the area of migration law and the problems and challenges that may arise.